PHYSIOLOGICALLY BASED PHARMACOKINETIC MODELS FOR ADULT AND PAEDIATRIC CHRONIC HEART FAILURE PATIENTS USING THE EXAMPLE OF CARVEDILOL TREATED PATIENTS. Issue 1 (14th December 2015) - Rasool, Muhammad; Khalil, Feras; Läer, Stephanie
Abstract : Background: In chronic heart failure (CHF), the changes in organ blood flows can significantly affect the metabolism of drugs with high hepatic extraction. Physiologically based pharmacokinetic modelling (PBPK) can be utilized to predict clearances of high extraction drugs like carvedilol in CHF. The adult PBPK-CHF model after its evaluation in adults, can be scaled to pediatrics using population based PBPK simulator. Methods: After a literature search for model input parameters, two-PBPK models were developed which differed only on the basis of clearance as, model-1 was based on human liver and intestinal microsomes clearance and model-2 was based on cytochrome-P450 clearances. Developed models were evaluated in healthy adults and in adult CHF patients, after incorporation of reduced organ blood flows. The evaluated adult CHF models were finally scaled to pediatric CHF patients using population based simulator Simcyp®. A two-fold error range for the ratios(Obs/Pred) of the pharmacokinetic parameters was used for model evaluation. Results: The prediction results from both models were within the 2-fold error range but the initial absorption phase after oral drug application was slightly over predicted with model-1 on the other hand, the model-2 efficiently captured the oral absorption phase. The CL/F ratios(Obs/Pred) were clearly improved after incorporation of reduced organ blood flows in adult CHF patients. In pediatrics CHF patients, improvement in predictions were seen only in adolescents above 17 years of age, staged with NYHA system of classification. Conclusion: There was a clear link between reduced organ blood flows and reduced carvedilol clearance in adult patients with CHF. It was suggested that Ross scoring system in pediatrics was not well correlated with organ blood flow reductions as the NYHA classification system. Due to the mechanistic nature of the developed models, they can be extended to other drugs with high hepatic extraction. The research leading to these results has received funding from the European Union Seventh Framework Programme (FP7/2007–2013) under grant agreement n°602295 (LENA) and from the Faculty Development Program BZ University Multan, Pakistan.